Writing assessment strategies for online learning during pandemic era - Jihan Khansa; Dyah Mukaromah (Politeknik Negeri Bali, 2022)
Online learning is a new challenge for educators who must master the use of digital media to support learning to run smoothly. Similar to offline learning, online learning still requires various assessment activities to evaluates students' mastery of English subject. Therefore, the English teachers at SMK Bhakti Husada PGRI Blora uses various assessment models in online learning, especially in students' writing skills. This is done for the reason that the teacher wants to improve students' writing skills, especially in English. Teachers use several assessment models during online learning, including handwriting, completing blank space, picture description, grammatical tasks, scrambled words, and short answer question tasks. Teachers use various models of writing assessment so that the assessment given to students will have more variety. The purpose of this study was to describe the assessment strategy used by the English teacher at SMK Bhakti Husada PGRI Blora for online learning during pandemic era, especially in writing skills. This study also indicates the appropriateness of those assessment strategies with four principles of language assessment.